2021
DOI: 10.34067/kid.0005372020
|View full text |Cite
|
Sign up to set email alerts
|

AKI in COVID-19–Associated Multisystem Inflammatory Syndrome in Children (MIS-C)

Abstract: Background: Multisystem Inflammatory Syndrome in Children (MIS-C) is a recently identified entity in association with COVID-19. Acute kidney injury (AKI) has been widely reported in patients with primary COVID-19 infection. However, there is a paucity of literature regarding renal injury in MIS-C. We aim to characterize AKI in MIS-C in this cohort identified at a major children's hospital in New York City during the COVID-19 pandemic. Methods: We conducted a retrospective cohort study of children 0-20 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Skin rash, which appeared in the early course of illness of our patient, is another cardinal sign of MIS-C. Our findings agree with previous findings that 36–81% of MIS-C patients had rash [ 45 , 47 , 55 61 ]. Laboratory findings of our case are in keeping with similar publications on leukopenia and thrombocytopenia [ 20 , 62 , 63 ] high ferritin, abnormal D-dimer, and elevated troponin [ 20 , 46 , 64 , 65 ]. In contrast to other findings, acute kidney injury (AKI) [ 64 , 66 69 ], prolonged coagulation profile, abnormal fibrinogen, and abnormal liver function[ 70 73 ] were not observed in our case.…”
Section: Discussionsupporting
confidence: 91%
“…Skin rash, which appeared in the early course of illness of our patient, is another cardinal sign of MIS-C. Our findings agree with previous findings that 36–81% of MIS-C patients had rash [ 45 , 47 , 55 61 ]. Laboratory findings of our case are in keeping with similar publications on leukopenia and thrombocytopenia [ 20 , 62 , 63 ] high ferritin, abnormal D-dimer, and elevated troponin [ 20 , 46 , 64 , 65 ]. In contrast to other findings, acute kidney injury (AKI) [ 64 , 66 69 ], prolonged coagulation profile, abnormal fibrinogen, and abnormal liver function[ 70 73 ] were not observed in our case.…”
Section: Discussionsupporting
confidence: 91%
“…This group found that renal involvement was associated with a greater elevation of CRP, ferritin, and procalcitonin, with greater lymphopenia and left ventricular dysfunction. It is suggested that the risk factors for acute kidney injury in children with MIS-C are greater age, greater inflammatory involvement, and ventricular dysfunction (28,30,31). In our study, we found high CRP and ferritin, indicative of a significant inflammatory response, along with frequent ventricular dysfunction,which might explain, in part, the frequency of AKI seen.…”
Section: Discussionsupporting
confidence: 56%
“…Although the pathophysiological mechanisms are unknown, we believe that in our study, delayed consultation, the lack of early recognition, the more significant inflammatory response, and frequent cardiovascular involvement, among others, may explain this greater frequency of kidney injury. Adults report 20% of kidney involvement in COVID-19, which may reach 50% in ICU patients, with a frequent need for continuous renal replacement therapy (28,29). In children with MIS-C, LiptonM et al ( 28) described 26 patients with acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%
“…A variable proportion (5–73%) of MIS-C patients have been found to have AKI ( 2 , 3 ). The pathophysiology of renal dysfunction in patients with SARS-CoV-2 infection is multifactorial including dehydration, poor cardiac output, cytokine storm, direct cytopathic effect of the virus on the renal tubular cells and use of nephrotoxic agents ( 5 ) whereas in patients presenting with MIS-C renal hypo-perfusion seems to be the major underlying factor for development of AKI ( 6 ). We conducted a retrospective chart review of pediatric patients with SARS-CoV-2 infection with or without MIS-C admitted to our hospital during the initial surge of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%